(untitled) (Libya Journal of Geographical Studies, 2023)
Al-Batnan region in northeastern Libya, and the research relied to study this phenomenon on climatic data, temperature, humidity, precipitation, sailing, wind speed, and frequency of dust storm days for the time period (1970-2010) for the two different study area stations in natural conditions such as the geographical and astronomical location and the height above sea level, Tobruk station In the northern parts of the Al-Batnan region, and Al-Jaghbub station in its southern parts, and through the results obtained, the study proved that there is a seasonal variation in the recurrence of dust storms, as the highest rate was recorded in late spring, as a result of the passage of depressions, high temperature, the beginning of soil drying, and the occurrence of a water deficit. It reflects negatively on the soil, making it easier to stir up dust compared to the winter season when the soil still retains its moisture.